Relationality in transaction cost economics and stakeholder theory: A new conceptual framework - Vladislav Valentinov; Steffen Roth (Business Ethics, the Environment & Responsibility, 2024)
Stakeholder scholars have long explored how stakeholder relationships differ from economic transactions. We contribute to this ongoing inquiry by developing a conceptual framework of relationality in stakeholder theory that encompasses a stakeholder-theoretic extension of Williamson's contracting schema and a new typology of stakeholder relationships. Premised on understanding relationality as the need for informal human relationships beyond formal governance, our framework locates the key difference between transaction cost economics and stakeholder theory in their treatment of informal relationships. While transaction cost economics perceives informal relationships to be shaped by formal governance structures and enforced by contractual safeguards, stakeholder theory is open to the possibility that some informal relationships between stakeholders may be genuinely moral and thus irreducible to formal governance and contractual safeguards. These stakeholder relationships may lead to unique economic effects described by instrumental stakeholder theory. The difference that we identified between the two literatures shows how stakeholder theory's embrace of relationality surpasses that of transaction cost economics.
Keywords: 330; stakeholder relationships; stakeholder theory; transaction cost economics; transactions